SOIi^E OBSERVATIONS ON THE CARP FRY RESOURCES OF THE RIVER GODAVARI NEAR RAJAHMUNDRY, ANDHRA PRADESH - Ibrahim, K H (Indian Journal of Fisheries, 2011)
AVAILABLE information on the fish seed resources, particularly of peninsular rivers and the quality and quantity of fish spawn collected therefrom, is rather fragmentary. Chacko (1946) mentions about the spawning of the major carps Catla catla, Labeo fimbriatus, Labeo calbasu and Cirrhina cirrhosa in the Godavari and the Krishna from July to September. According to him Catla predominates (60%) in the fry and fingerlings collected from the canals and paddy fields; while in the river collections, fry of L. fimbriatus (60%) predominate. AUkunhi (1947) recorded the natural occurrence of Cirrhina mrigala in the Godavari and found the species forming about 20% of the total fish landings at Rajahmundry. Alikunhi et al. (1949) collected eggs and hatchUngs of L., calbasu in large numbers from the Godavari below the anicut at Bobberlanka, on 22-7-1948